Operations management an integrated approach - Reid, Robert D (Wiley, 2005)
Focusing on how Operations Management (OM) fits into the business environment, this book takes OM beyond the factory setting by illustrating how OM is everywhere. By approaching the subject in an applied fashion, it introduces readers to all aspects of OM and allows them to immediately apply that knowledge to the business environment. Continuing on the success of the first edition, this new edition includes increased use of spreadsheets, more problems and case studies, and new and expanded coverage of the role of OM in the organization. In addition, it covers such current topics as Enterprise Resource Planning (ERP) and periodic order review.